Downsizing Recognizing the Effects and Taking Control - Lynch, Jemma (Operating Room Nurses Association of Canada Journal, 1993)
The first part of this article will address the effects of displacement or bumping on staff, the second part will outline some strategies which have been found helpful in organizational downsizing, and the ﬁnal part will describe Layoff Survivor Sickness as out- lined in “Healing the Wounds” by David Noer.